Use of tuf as a target for sequence-based identification of Gram-positive cocci of the genus Enterococcus, Streptococcus, coagulase-negative Staphylococcus, and Lactococcus - Li Xuerui; Xing Juan; Li Baoyu; Wang Pu; Liu Jixing (Annals of Clinical Microbiology and Antimicrobials, 2012)
Abstract Background Accurate identification of isolates belonging to genus Enterococcus, Streptococcus, coagulase-negative Staphylococcus, and Lactococcus at the species level is necessary to provide a better understanding of their pathogenic potential, to aid in making clinical decisions, and to conduct epidemiologic investigations,especially when large blind samples must be analyzed. It is useful to simultaneously identify species in different genera using a single primer pair. Methods We developed a primer pair based on the tuf gene (encoding elongation factor) sequence to identify 56 Gram-positive cocci isolates. Results The target sequences were amplified from all 56 samples. The sequencing results and the phylogenetic tree derived from the partial tuf gene sequences identified the isolates as three enterococcal species, two lactococcal species, two staphylococcal species, and six streptococcal species, as well as eight isolates that were novel species of the genus Streptococcus. Partial gene sequence analysis of the sodA, dnaK, and 16S RNA genes confirmed the results obtained by tuf gene sequencing. Conclusion Based on the uniform amplification of the tuf gene from all samples and the ability to identify all isolates at both the genus and species levels, we conclude that the primer pair developed in this research provides a powerful tool for identifying these organisms in clinical laboratories where large blind samples are used.